The Effects of Portulaca Supplementation on Antioxidant Biomarkers and Oxidative Stress in non-Active Girls - B Ghorbanian; Y Saberi; K Azali Alamdari; F Shokrollahi; H Mohammadi (Institue of Medicinal Plants, ACECR, 2019)
Background: Oxidative stress results from imbalance in the bodychr('39')s redox position, which results in tissue damage due to increased intracellular radicals. Antioxidants prevent the oxidation of fatty acids and prevent foam cells and atherosclerotic plaque. Portulaca, which is one of the supplements, is considered as an antioxidant-rich plant. Objective: The purpose of this study was to evaluate the effect of eight weeks of Portulaca supplementation on antioxidant enzymes and oxidative stress in non-active girls. Methods: This quasi-experimental study was conducted on non-active girls (overweight and obese) with an age range of 20-30 years in Azarbaijan Shahid Madani University. 20 subjects were qualified and randomly divided into two control (n = 10) and complement (n = 10) groups. Subjects of supplemented group received 1200 portulaca mg per day for eight weeks. Data were analyzed by t-test using by SPSS20 software. Statistical significance criterion was set as P<0.05. Results: The results showed that serum levels of superoxide dismutase (SOD), glutathione peroxidase(GPX) and total antioxidant capacity (TAC) were significantly increased in the supplemented group (P<0.05), while the amount of malondialdehyde (MAD) decreased, this decline was not statistically significant (P> 0.05). Conclusion: Portulaca supplements are likely to be effective in improving cardiovascular health and preventing cardiovascular disease and strengthening the antioxidant system in overweight and obese people, and destroys lipid peroxidation that produces ROS.